Factors Affecting Teacher’s Absenteeism in Secondary School of Kathmandu Valley - Khadka, Sabin; Pradhan, Sumit (Nepalese Journal of Management, 2025)
This study examines the factors affecting teacher’s absenteeism in secondary school of Kathmandu Valley. Absenteeism is the dependent variable. The selected independent variables are job stress, working condition, performance appraisal, motivation and health condition. The primary sources of data is used to assess the opinions of respondents regarding job stress, working condition, performance appraisal, motivation, health condition and absenteeism. The study is based on the primary data of 127 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of factors affecting teacher’s absenteeism in secondary school of Kathmandu Valley. The study showed a positive impact of job stress on absenteeism. It indicates that higher the job stress, higher would be the absenteeism. Similarly, the study showed a negative impact of health condition on absenteeism. It indicates that good health condition of teachers leads to decrease in absenteeism. Likewise, the study showed a negative impact of performance appraisal on absenteeism. It indicates that fair performance appraisal mechanism leads to decrease in absenteeism. In addition, the study also showed a negative impact of motivation on absenteeism. It indicates that motivation programs organized for the teacher leads to decrease in absenteeism. Further, the study showed a negative impact of working condition on absenteeism. It indicates that friendly working environment leads to decrease in absenteeism of teachers.